A Project Report for COFARM - Jonathan Ariel Muyeti (My University, 2024)
The coffee industry frequently has difficulties with fair pricing, market access, and communication between buyers and farmers, especially in areas like Uganda. The present dissertation delves into the creation and execution of COFARM, a mobile application that aims to strengthen coffee farmer unions and augment their revenue streams by establishing a connection between producers and consumers. The report lists the main difficulties that coffee farmer unions confront, such as their restricted distribution options, confusing price structures, and communication gaps. In order to address these issues and advance sustainable practices, COFARM will be developed through extensive study and stakeholder participation. The primary goals of COFARM are to create an intuitive marketplace, apply open pricing policies, and enable direct connection between buyers and producers. Coffee farmer unions can post their products on the marketplace with thorough descriptions and information about their origins, and safe payment gateways guarantee easy transactions. Long-term partnerships and trust are fostered by transparent pricing algorithms, which take market trends and quality into account. A communication platform also facilitates real-time negotiation and interaction, which improves relationship-building and personalized orders. This study is important because it might strengthen coffee farmer unions, advance fair trade and transparency, and provide small-scale growers with more access to markets. COFARM seeks to support the sustainability and economic success of the coffee industry in Uganda and abroad by offering a digital solution that is customized to meet the demands of coffee buyers and growers.